Effect of Family, Community and Education Environment on Prevention of Drug Abuse in High School Students - Supli Effendi Rahim; Yulestri Yulestri; Amar Muntaha; Dianita Ekawati Ekawati; Hamyatri Rawalilah; Ali Harokan; Husin Husin (Sriwijaya Journal of Environment, 2020)
Teenagers are the spearhead of the progress and development of the nation and state. Therefore they must not be involved in drug abuse. This paper tries to report the results of a study that examines the relationship between family environment, community and education with drug abuse in I Lawang Wetan Musi Banyuasin Vocational High School in 2018. This study is a cross sectional study using a sample of 82 respondents. Data were collected and analyzed univariate, bivariate and multivariate. The results of the study show that the family environment, community environment and educational environment have a close relationship with the prevention of drugs. Statistically all of these variables are significantly related to efforts to drug abuse prevention. Two important variables that determine drug prevention efforts for students in the school are the family environment and the community environment. In order to succeed in drug abuse prevention efforts it is recommended that education about drugs be given to students, schools need collaboration with parents and cooperation with local communities.